Light‐Powered Microrobots: Challenges and Opportunities for Hard and Soft Responsive Microswimmers. (22nd February 2021) - Bunea, Ada‐Ioana; Martella, Daniele; Nocentini, Sara; Parmeggiani, Camilla; Taboryski, Rafael; Wiersma, Diederik S.
Abstract : Worldwide research in microrobotics has exploded in the past two decades, leading to the development of microrobots propelled in various manners. Despite significant advances in the field and successful demonstration of a wide range of applications, microrobots have yet to become the preferred choice outside a laboratory environment. After introducing available microrobotic propulsion and control mechanisms, microrobots that are manufactured and powered by light are focused herein. Referring to pioneering works and recent interesting examples, light is presented not only as a fabrication tool, by means of two‐photon polymerization direct laser writing, but also as an actuator for microrobots in both hard and soft stimuli–responsive polymers. In this scenario, a number of challenges that yet prevent polymeric light‐powered microrobots from reaching their full potential are identified, whereas potential solutions to overcome said challenges are suggested. As an outlook, a number of real‐world applications that light‐powered microrobots should be particularly suited for are mentioned, together with the advances needed for them to achieve such purposes. An interdisciplinary approach combining materials science, microfabrication, photonics, and data science should be conducive to the next generation of microrobots and will ultimately foster the translation of microrobotic applications into the real world. Abstract : Light is an excellent tool for the fabrication and manipulation of microrobots. Two‐photon polymerization enables DLW of extremely fine structures in different polymer formulations. For hard microrobots, optical trapping enables extremely precise manipulation, whereas soft microrobots can be cleverly engineered to change shape in controlled fashion in response to light.